KEPEMILIKAN ASURANSI KESEHATAN DAN PEMANFAATAN PELAYANAN KESEHATAN OLEH PENDUDUK LANJUT USIA DI KOTA TARAKAN - , Fitri Damayanti; , Dr. drg. Julita Hendrartini, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Life expectancy has been one of the indicators in measuring the development of human index in a country. It has implications to the increase of the elderly each year. This situation is mostly unparalleled with the ease of access to health services, health insurance coverage and health program. Health facilities gave less attention and services to elderly, which would cause lower number of health services utilization provided by the government in Indonesia. This research aims to identify and analyze the factors that affect health services utilization among elderly in Tarakan. Method: This analytic study using cross sectional survey design with quantitative approach. Primary data collected using questionnaire to the elderly over 60 years old in Tarakan with simple random sampling techniques to 345 respondents. Statistical analysis used univariable, bivariable, and multivariable. Result: In 2010, 13,9% of elderly in Tarakan were insured and 86,1% had public coverage. This study found that variables of cost sharing, the perceived to illnesses, and the distance to the healths facilities (hospital) had significant affected to the health service utilization by elderly people in Tarakan (p<0,05). Whilst variables of ability to pay, health insurance ownership, transportation, and health service facilities have no significant affected to the health service utilization among the elderly. Conclusion: The specific needs of elderly warrant consideration ongoing development programme in Tarakan and evaluation of policies aimed at reducing uncompensated care costs. More attention is needed to improve the utilization of health care with expand access and coverage health insurance for elderly with inadequate insurance coverage